Allocation procedure in ethanol production system from corn grain. - Kim, Seungdo
We investigated the system expansion approach to net energy analysis for ethanol production from domestic corn grain. Production systems included in this study are ethanol production from corn dry milling and corn wet milling, corn grain production (the agricultural system), soybean products from soybean milling (i.e. soybean oil and soybean meal) and urea production to determine the net energy associated with ethanol derived from corn again. These five product systems are mutually interdependent. That is, all these systems generate products which compete with or displace all other comparable products in the market place. The displacement ratios between products compare the equivalence of their marketplace functions. The net energy, including transportation to consumers, is 0.56 MJnet/MJ of ethanol from corn grain regardless of the ethanol production technology employed. Using ethanol as a liquid transportation fuel could reduce domestic use of fossil fuels, particularly petroleum. Sensitivity analyses show that the choice of allocation procedures has the greatest impact on fuel ethanol net energy. Process energy associated with wet milling, dry milling and the corn agricultural process also significantly influences the net energy due to the wide ranges of available process energy values. The system expansion approach can completely eliminate allocation procedures in the foreground system of ethanol production from corn grain.
Keywords: Allocation; Corn; Ethanol; Life cycle assessment; Net energy; Sensitivity analysis; System expansion